Every Cancer Narrative Is an Act of Life: A conversation with Nancy K. Miller (January and February 2020) (Altre Modernità, 2020)
Every Cancer Narrative Is an Act of LifeA conversation with Nancy K. Miller (January and February 2020)by Leonardo Nolé